Field notes on the breeding biology and diet of ferruginous pygmy-owl (Glaucidium brasilianum) in the dry chaco of Argentina - Carrera, J.D. (2008)
Fil:Fernández, F.J. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales; Argentina.